(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Gestational diabetes mellitus, also known as or GDM and diabetic disorders Type 1 diabetes is brought on by the immune response destroying pancreatic cells. 5–10% of diabetes diagnosed in the entire population is caused by it. The aim is to evaluate the effects of the variables on experimental and control groups’ of the recurrence of GDM in antenatal mothers. Methodology are based on purposive sampling technique. Antenatal mothers in the experimental group attended the video teaching at their first antenatal visit (6-12 weeks). Video training focused mainly on group walking, dietary modification, monitoring body weight and maintaining BMI and modifying the sleeping pattern. Results are antenatal mother background variables, the majority of females in the group performing the experiment were between the ages of 31 and 35; 21 (52.5%); had completed their college education; 28 (70%); were housewivesAmong the antenatal mothers in the control group, the majority were between the ages of 26 and 30; 23 (57.5%) had completed their college educations; 30 (75.5%) were housewives. the majority of women in those in the experiment had BMIs over 25, 36 (90%), as well as waist-hip ratios more than 0.85, 38 (95%). had done their housework with help 38(95%). The factors that lead to continued resistance to insulin in GDM are expected to be as varied as in the wider community given that GDM represents a spectrum of young women suffering a tolerance for glucose. The factors are age, educational status, family, health information are responsible for the GDM in antenatal mothers.